Studi Eksplanatori; Penerapan Standar Pelayanan Antenatal Pada Kasus Kematian Ibu - Made Widhi Gunapria Darmapatni; Ni Wayan Ariyani (Poltekkes Kemenkes Denpasar, 2021)
Maternal Mortality Rate is the death of a woman during pregnancy, childbirth, or within 42 days after the end of the pregnancy, which is caused by direct and indirect causes. The study purpose is to determine the application of antenatal care standards for maternal mortality and to explore perceptions of inhibiting and supporting factors. This type of study is mixed (mixed methodology). In the quantitative stage with a descriptive approach, it is followed by a qualitative analysis stage. The locations is in public health, maternity clinics, hospitals where maternal mortality. The population is all cases of maternal mortality in the regencies / municipalities of Bali Province in 2016 till September 2017. The most characteristic of maternal deaths is dominant happened to mother with age 31 untill 35 years old, education from that mothers in elementary, housewife, had 1-2 child was born, the distance to health facility 6 – 10 kilometers and there are BPM and public health. The health care provider is 100% a health worker, 57,5% given by antenatal care which had 4 times visit during pregnancy, 89,4% had a complete antenatal care with 10T. The direct cause is the highest cause of death 26 case (55.3%) The support factor are widsom from government, patnership, human resourses and monitoring. The barrier factor are reconciliation, perception and human resourses. Therefore necessary to conduct a similar study with control groups and interviews in triangulation lo eksplore cause of mortality .